Biocompatibilidade de matrizes de colágeno aniônico e sua influência na orientação do crescimento celular - Buchaim, Rogério Leone (2004)
The present study was aimed at examining the biocompatibility of anionic collagen matrices, their local bone response following implantation in surgically-created bone defects and also the influence of the collagen fiber orientation in the neoformed bone tissue. Seventy two rats ( Rattus norvegicus albinus ) were used in this experiment. The animals were divided into four experimental groups: Group 1 (control), without implants; Group 2, pericardium medullar implants, 12 hours; Group 3, medullar implants of tendon, 24 hours, with the bigger axes of collagen fibers parallel to the bigger axes of the tibia; and Group 4, medullar implants of tendon, 24 hours, with the bigger axes of collagen fibers perpendicular to the bigger axes of the tibia. After the experimental surgery, the evolution of the repair process was microscopically evaluated in 7, 15 and 30 days post-surgery. The results demonstrated the implanted matrices to be biocompatible and to function as a scaffold inducing the formation of bone, mainly in Group 4. At first, the cellularity follows the arrangement of collagen fibers, obtaining a growing multidirectional arrangement, suggesting that the direction and the orientation are related to the direction and to the magnitude of the stress applied to the bone.